Path analysis of soybean yield in the micro region of Alto Médio Gurguéia - Alcantara Neto, Francisco de; Gravina, Geraldo de Amaral; Monteiro, Marinete Martins de Sousa; Morais, Fernanda Brito de; Petter, Fabiano André; Albuquerque, José Anchieta Alves de (Comunicata Scientiae, 2011)
The objective of this work was to evaluate, by using path analysis, the influence of some agronomic characters on soybean yield. An experiment was conducted in cerrado soil, in Serra do Quilombo, Bom Jesus, Southern of Piaui State, from december 2007 to april 2008, in an Oxisol. The experimental design was randomized blocks, with treatments consisting of six levels of phosphorus (0, 40, 60, 100, 120 and 140 kg P2O5 ha-1) with four replications. Some characteristics were evaluated: plant height, height of first pod insertion, number of nodes per plant, number of string beans per plant, 100 grains weight, dry weight and total grain production per plant. The number of pods per plant was the yield component that showed the greatest direct effect on dry matter and total grain production per plant. The number of nodes per plant had a strong indirect effect on dry matter production. The variable height of first pod insertion showed lower correlation with the other variables.